Carbon-coated cobalt-based electrocatalyst

By depositing CoO/NiCoP porous nanosheets on the surface of the carbon cloth, a double heterosurface CoO/NiCoP@CON catalyst was formed, and the problem of high overpotential in electrolytic hydrogen production technology was solved, and efficient electrocatalytic hydrogen evolution activity and stability were achieved. The commercial application of electrolytic water hydrogen production technology has been promoted.

CN222160389UActive Publication Date: 2024-12-13QINGDAO UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202323308664.8
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2023-12-06
Publication Date
2024-12-13
Estimated Expiration
2033-12-06

AI Technical Summary

Technical Problem

Due to the slow kinetic reaction and system resistance in the existing electrolytic hydrogen production technology, the overpotential is high, which restricts the commercial development of electrolytic hydrogen production technology, especially the scarcity and expensive price of precious metal Pt/C catalysts. Its large-scale application.

Method used

Carbon-coated cobalt-based electrocatalysts, including CoO/NiCoP porous nanosheets, were deposited on the surface of the carbon cloth by ultraviolet-assisted electrodeposition method to form a double heterosurface CoO/NiCoP@CON catalyst, which improves the electrocatalytic hydrogen evolution activity and stability. sex.

Benefits of technology

In an alkaline environment, the overpotential of 10mA/cm2 is reduced to 49mV, and the overpotential of 100mA/cm2 is required to reach 108mV, and the performance is stable for more than 50 hours, which is better than most transition metal phosphide catalysts and is expected to achieve electrolytic water Commercial application of hydrogen production technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222160389U_ABST
    Figure CN222160389U_ABST
Patent Text Reader

Abstract

The utility model relates to the technical field of hydrogen evolution electrocatalysts, in particular to a carbon-coated cobalt-based electrocatalyst which comprises carbon cloth serving as a substrate, a carbon-coated CoO / NiCoP porous nanosheet layer is deposited on the surface of the carbon cloth, the carbon-coated cobalt-based electrocatalyst shows excellent electrocatalytic hydrogen evolution activity in alkaline electrolyte, and the performance of the carbon-coated cobalt-based electrocatalyst is superior to that of most transition metal phosphide hydrogen evolution catalysts. Commercialized application of a large-scale water electrolysis hydrogen production technology is expected to be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of hydrogen evolution electrocatalysts, in particular to a carbon-coated cobalt-based electrocatalyst. Background Art

[0002] The electrolysis of water to produce hydrogen uses direct current as the energy source. The current moves between the positive and negative electrodes, causing the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) to release hydrogen and oxygen. Due to the slow kinetic reaction and the existence of system resistance in the process of electrolysis of water to produce hydrogen, an overpotential (η) will inevitably be generated during the electrolysis process, resulting in the actual required electrolysis potential being much higher than the theoretical value, which restricts the commercial development of the electrolysis of water to produce hydrogen technology. The development of efficient catalytic electrode materials can effectively reduce the inherent activation barriers of the hydrogen evolution reaction process, save electrical energy consumption, and reduce the cost of hydrogen production. At present, the precious metal Pt / C is recognized as the most efficient HER catalyst, which can effectively accelerate the hydrogen evolution kinetic reaction process, but the scarcity and high price of Pt are not conducive to its large-scale use in electrocatalytic hydrogen production. Therefore, the development of a non-precious metal-based, efficient and stable electrocatalyst that can replace Pt has become a research hotspot in the field of electrolysis of water to produce hydrogen.

[0003] Studies have shown that transition metal phosphides have excellent catalytic activity for hydrogen production by electrolysis of water. CN105951123A discloses a method for preparing a NiCoP nanowire electrocatalytic electrode, comprising the following steps: 1) pretreatment of the nickel surface to remove the oxide layer on the surface of the nickel foam; 2) hydrothermal growth of a nickel cobalt salt compound precursor, placing a nickel foam sheet in a solution containing nickel ions and cobalt ions, and sealing and baking in a high-pressure reactor, washing and drying to obtain a nickel cobalt salt compound precursor; 3) phosphating process of the nickel cobalt salt nanowire, calcining sodium dihydrogen hypophosphite powder and nickel cobalt salt / nickel foam sheet at 300-500°C for 3-5.5h under N2 protection, followed by natural cooling, and washing and drying the obtained product to obtain a NiCoP nanowire electrocatalytic electrode. Although the material is simple to prepare, the nanowire structure is uniform, and it exhibits HER activity, its overpotential is as high as 109mV at a current density of 10mA·cm2 in a 1M KOH electrolyte, and its electrocatalytic performance is poor. Summary of the invention

[0004] In view of the shortcomings of the above-mentioned prior art, a carbon-coated cobalt-based electrocatalyst is provided, which exhibits excellent electrocatalytic hydrogen evolution activity in alkaline electrolyte, and its performance is better than that of most transition metal phosphide hydrogen evolution catalysts, and is expected to realize the commercial application of large-scale water electrolysis hydrogen production technology.

[0005] In order to solve the above technical problems, the technical solution adopted by the utility model is a carbon-coated cobalt-based electrocatalyst, including a carbon cloth as a substrate, and a carbon-coated CoO / NiCoP porous nanosheet layer is deposited on the surface of the carbon cloth.

[0006] The carbon-coated cobalt-based electrocatalyst comprises CoO / NiCoP heterogeneous surfaces and NiCoP@CON heterogeneous surfaces.

[0007] The carbon-coated cobalt-based electrocatalyst can achieve a current of 10 mA / cm in an alkaline environment. 2 The overpotential required is 49mV to reach a current of 100mA / cm 2 The overpotential required is 108mV, and the performance can remain stable for more than 50 hours.

[0008] The above carbon-coated cobalt-based electrocatalyst has a Tafel slope of 59.2 mVdec -1 .

[0009] The carbon-coated cobalt-based electrocatalyst has a Cdl value of 86.3 mF / cm 2 .

[0010] The carbon-coated cobalt-based electrocatalyst has a carbon cloth having a size of 10 mm long x 10 mm wide.

[0011] The beneficial effects of a carbon-coated cobalt-based electrocatalyst of the present invention are:

[0012] The carbon-coated cobalt-based nanoheterostructured CoO / NiCoP@CON composite catalyst synthesized by the utility model has obvious advantages. The double heterogeneous surfaces (CoO / NiCoP heterogeneous surfaces and graphitized carbon-based heterogeneous surfaces NiCoP@CON) in the catalyst provide abundant active sites for the HER process; the charge transfer at the interface effectively regulates the electronic structure of the material; and the graphitized carbon improves the stability.

[0013] In alkaline environment (pH = 13.5), the current reaches 10mA / cm 2 The overpotential required is only 49mV to reach a current of 100mA / cm 2 The overpotential required is 108 mV, and the performance can remain stable for more than 50 hours. Its performance is better than that of most transition metal phosphide hydrogen evolution catalysts, and it is expected to realize the commercial application of large-scale water electrolysis hydrogen production technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is the XRD pattern of CoO / NiCoP@CON catalyst;

[0015] Figure 2 XPS spectrum of CoO / NiCoP@CON catalyst;

[0016] Figure 3 Scanning electron microscopy image of CoO / NiCoP@CON catalyst (2μm, 200nm);

[0017] Figure 4 is the SEM image of the comparative catalyst (2 μm, 200 nm);

[0018] Figure 5 Transmission electron microscopy image of CoO / NiCoP@CON catalyst;

[0019] Figure 6 Raman spectra of CoO / NiCoP@CON catalyst and comparative catalyst;

[0020] Figure 7 Polarization curves of CoO / NiCoP@CON catalyst and comparative catalyst in alkaline solution;

[0021] Figure 8 Tafel slope curves of CoO / NiCoP@CON catalyst and comparative catalyst in alkaline solution;

[0022] Fig. 9 The AC impedance diagram of CoO / NiCoP@CON catalyst in alkaline solution;

[0023] Fig.10 The double-layer capacitance fitting curve of CoO / NiCoP@CON catalyst in alkaline solution;

[0024] Fig.11 Polarization curves of CoO / NiCoP@CON catalyst in alkaline solution at the initial stage and after 2000 CV cycles;

[0025] Fig.12 This is the constant current electrochemical stability test curve of CoO / NiCoP@CON catalyst in alkaline solution. DETAILED DESCRIPTION

[0026] The utility model is described in detail below with reference to the accompanying drawings and specific embodiments.

[0027] A carbon-coated cobalt-based electrocatalyst comprises a carbon cloth as a substrate, on the surface of which a carbon-coated CoO / NiCoP porous nanosheet layer (denoted as CoO / NiCoP@CON) is deposited.

[0028] Example 1

[0029] The above-mentioned method for preparing a carbon-coated cobalt-based electrocatalyst comprises the following steps:

[0030] (1) Substrate pretreatment: Soak the carbon cloth in a dilute hydrochloric acid solution, heat to 80°C, reflux for 180 minutes, and finally wash it repeatedly with deionized water and anhydrous ethanol, and dry it for later use;

[0031] (2) Precursor preparation: A three-electrode system is used to prepare a catalyst precursor deposited on the surface of the carbon cloth by UV-assisted electrodeposition. The deposition voltage is -0.75 V to -1 V, the time is 1200 s, the temperature is 75°C to 85°C, and the UV wavelength is 254 nm to 365 nm. After the UV-assisted electrodeposition is completed, the carbon cloth is washed with ethanol and water respectively, and finally dried for use.

[0032] (3) Preparation of catalyst: The carbon cloth loaded with the catalyst precursor is placed in the center of a tubular furnace for graphitization and phosphating reaction: in an argon atmosphere, the temperature is increased from room temperature to 350°C at a heating rate of 3°C / min and maintained at this temperature for calcination for 2 h; then the mixture is switched to a PH3 atmosphere and the temperature is maintained at 300-400°C for 2 h. Finally, the mixture is cooled naturally to obtain a double heterogeneous CoO / NiCoP@CON porous nanosheet electrocatalyst grown on the surface of the carbon cloth.

[0033] The above-mentioned method for preparing carbon-coated cobalt-based nano-heterostructure electrocatalyst by ultraviolet-assisted electrodeposition, the three-electrode system uses Ag / AgCl electrode as reference electrode, carbon rod as auxiliary electrode, and carbon cloth as working electrode.

[0034] The utility model synthesizes a high-performance double heterogeneous surface CoO / NiCoP@CON porous nanosheet hydrogen evolution electrocatalyst grown on the surface of carbon cloth by ultraviolet-assisted electrochemical deposition. The catalyst has abundant active sites and excellent electronic structure, exhibits excellent electrocatalytic hydrogen evolution activity in alkaline electrolyte, and has a simple preparation process, which reduces the preparation temperature required for graphitization of carbon in the composite material. The raw materials are low in price and abundant in source, and are suitable for industrial large-scale production.

[0035] Example 2

[0036] The similarities between this embodiment and embodiment 1 are not repeated here. The difference lies in: a method for preparing a carbon-coated cobalt-based electrocatalyst, wherein in step (2), the deposition voltage is -0.85 V, the time is 1200 s, the temperature is 84° C., and the ultraviolet wavelength is 354 nm.

[0037] In the step (3), under an argon atmosphere, the temperature is raised from room temperature to 340°C at a heating rate of 3°C / min, and this temperature is maintained for calcination for 2 hours; then, the mixture is switched to a PH3 atmosphere and the temperature condition of 310°C is maintained for 2 hours.

[0038] Comparative example: repeat step (1), change the deposition conditions in step (2) to no UV assistance, keep other conditions unchanged, and repeat experimental step (3).

[0039] Figure 1The XRD pattern of the prepared composite catalyst shows a strong diffraction peak at 2θ≈26° in the XRD pattern of CoO / NiCoP@CON, which is consistent with the XRD result of carbon cloth, indicating that the prepared catalyst has been successfully grown on the surface of carbon cloth. In addition, the characteristic diffraction peaks of the CoO / NiCoP@CON catalyst material at 36.5°, 42.5°, 61.5° and 73.6° correspond to the (111), (200), (220) and (311) crystal planes of CoO (PDF#48-1719).

[0040] Figure 2 The chemical composition and electronic structure of the catalyst surface are shown. X-ray photoelectron spectroscopy (XPS) shows that the peak at 779.1 eV belongs to the Co 2p3 / 2 orbital, corresponding to the Co-P bond ( Figure 2 a), while the peak at 853.9 eV corresponds to the Ni-P bond ( Figure 2 b), for the P 2p spectrum, such as Figure 2 As shown in (c), the peaks at 129.5eV and 130.65eV in the CoO / NiCoP@CON sample are attributed to negatively charged phosphorus species, namely, MP chemical bonds (M represents metal), which proves the existence of NiCoP crystal phase. Figure 2 As shown in Figure d, the C1s peak of the electrocatalyst can be fitted to C=C (284.7 eV), CN (285.7 eV) and C=O (289.2 eV). Figure 2 e proves the existence of pyridinic nitrogen and graphitized nitrogen. The peak at 531.5 in the O1s spectrum can be attributed to the OM chemical bond. In summary, the catalyst surface contains not only NiCoP compounds but also graphitized carbon doped with O and N. Combined with the XRD characterization results, the specific composition of the catalyst is CoO / NiCoP@CON.

[0041] Figure 3 The morphology of CoO / NiCoP@CON is shown, and the regularly arranged nanosheet structure grown on the surface of the carbon cloth can be clearly observed at both large and small resolutions.

[0042] Figure 4 The morphology of the comparative catalyst prepared without UV irradiation is shown. Figure 3 In comparison, it can be clearly observed that the catalyst with nanosheet structure is irregularly arranged on the surface of carbon cloth, and the surface of carbon cloth is not evenly covered by the comparison catalyst.

[0043] Figure 5The transmission electron microscopy (TEM) image of the CoO / NiCoP@CON catalyst is shown. It is not difficult to find that the CoO / NiCoP is embedded in the N and O doped graphitized carbon structure, and the internal CoO / NiCoP presents a porous structure. Figure 5 (a)] and form a heterogeneous interface through PO coupling. In addition, the lattice fringes in different directions can be clearly observed through high-resolution transmission electron microscopy (HRTEM) images [ Figure 5 (b)], the stripes with lattice spacing of 0.21nm, 0.24nm and 0.22nm can be attributed to the (100) crystal plane of graphitized carbon, the (111) crystal plane of CoO and the (111) crystal plane of NiCoP phase, respectively, which once again proves the existence of CoO crystal phase and small particles of NiCoP crystal phase, which are embedded in the interior of the graphitized carbon structure.

[0044] Figure 6 The Raman spectra of CoO / NiCoP@CON, comparative catalyst and carbon cloth are shown. It can be found from the figure that the proportion of graphitized carbon in CoO / NiCoP@CON catalyst and comparative catalyst is higher than that in carbon cloth, which proves the formation of graphitized carbon in the product. In addition, the proportion of graphitized carbon in CoO / NiCoP@CON catalyst reaches the highest, which proves that ultraviolet light plays a decisive role in the formation of graphitized carbon.

[0045] like Figure 7 As shown in the figure, under alkaline conditions (1 mol / L NaOH), based on the CHI760E electrochemical workstation and three-electrode system, the electrochemical performance of CoO / NiCoP@CON and the comparative catalysts was tested. It can be seen from the linear sweep (LSV) curve that 10 mA / cm 2 Under the current density, the overpotential required for the CoO / NiCoP@CON composite catalyst is only 49 mV, which is significantly better than the hydrogen evolution catalytic activity of the control catalyst (104 mV) under the same conditions.

[0046] like Figure 8 As shown, the Tafel slopes of the Co / NiCoP@CON catalyst and the comparative catalyst are 59.2 mV / dec and 103.6 mV / dec, respectively. It is obvious that the Co / NiCoP@CON catalyst has superior reaction kinetics.

[0047] In order to further analyze the hydrogen evolution reaction activity of the catalyst, electrochemical impedance spectroscopy (EIS) was used to evaluate the charge transfer ability of the catalyst. Fig. 9 This is the Nyquist curve of the Co / NiCoP@CON catalyst. It can be seen that the Co / NiCoP@CON catalyst has a small resistance, which means it has a strong conductivity.

[0048] like Fig.10 As shown in Figure 2, the calculated Cdl value of the Co / NiCoP@CON catalyst is 86.3 mF / cm 2 , and its active specific surface area is far superior to that of most reported non-precious metal catalysts.

[0049] like Fig.11 As shown, the Co / NiCoP@CON catalyst was subjected to 2000 voltammetric scanning cycle stability tests. The results showed that there was no obvious difference in the LSV curves of the catalyst before and after the test, proving the good electrochemical stability of the catalyst.

[0050] like Fig.12 As shown, at 10mA / cm 2 and 50mA / cm 2 At a current density of , the electrochemical stability experiment of Co / NiCoP@CON catalytic electrode was carried out for 50 h. In the 50 h constant potential test, the potential decrease trend of the catalyst was small, which once again proved its electrochemical stability.

[0051] Example 3

[0052] The similarities between this embodiment and embodiment 1 are not repeated here, and the difference lies in: a method for preparing a carbon-coated cobalt-based electrocatalyst, wherein in step (2), the precursor is prepared by using a three-electrode system to prepare a catalyst precursor deposited on the surface of a carbon cloth by ultraviolet-assisted electrodeposition, the deposition voltage is -1.0 V, the time is 1200 s, the temperature is 85° C., and the ultraviolet wavelength is 365 nm; after the ultraviolet-assisted electrodeposition is completed, the carbon cloth is washed with ethanol and water respectively, and finally dried for use;

[0053] (3) Preparation of catalyst: The carbon cloth loaded with catalyst precursor is placed in the center of a tubular furnace for graphitization and phosphating reaction: in an argon atmosphere, the temperature is increased from room temperature to 350°C at a heating rate of 3°C / min and maintained at this temperature for calcination for 2 h; then, it is switched to a PH3 atmosphere and the temperature is maintained at 400°C for 2 h. Finally, the temperature is naturally cooled to obtain a double heterogeneous CoO / NiCoP@CON porous nanosheet electrocatalyst grown on the surface of the carbon cloth.

[0054] Example 4

[0055] The utility model discloses a carbon-coated cobalt-based electrocatalyst, which can achieve a current of 10 mA / cm in an alkaline environment (pH = 13.5). 2 The overpotential required is only 49mV to reach a current of 100mA / cm 2 The overpotential required is 108 mV, and the performance can remain stable for more than 50 hours. Its performance is better than that of most transition metal phosphide hydrogen evolution catalysts, and it is expected to realize the commercial application of large-scale water electrolysis hydrogen production technology.

[0056] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A carbon-coated cobalt-based electrocatalyst, characterized in that: It includes a carbon cloth as a substrate, and a carbon-coated CoO / NiCoP porous nanosheet layer grown on the surface of the carbon cloth, which includes a CoO / NiCoP heterogeneous surface and a NiCoP@CON heterogeneous surface. The CoO / NiCoP@CON grown on the surface of the carbon cloth is a regularly arranged nanosheet structure, and the CoO / NiCoP presents a porous structure.

2. The carbon-coated cobalt-based electrocatalyst according to claim 1, characterized in that: In alkaline environment, the current reaches 10mA / cm 2 The overpotential required is 49mV to reach a current of 100mA / cm 2 The overpotential required is 108mV, and the performance can remain stable for more than 50 hours.

3. The carbon-coated cobalt-based electrocatalyst according to claim 2, characterized in that: The Tafel slope is 59.2mVdec -1 .

4. The carbon-coated cobalt-based electrocatalyst according to claim 3, characterized in that: Its Cdl value is 86.3mF / cm 2 .

5. The carbon-coated cobalt-based electrocatalyst according to claim 4, characterized in that: The carbon cloth has a specification of 10 mm long×10 mm wide.